1992
DOI: 10.1002/jcp.1041520113
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of albumin expression in fetal rat hepatocytes cultured under proliferative conditions: Role of epidermal growth factor and hormones

Abstract: Sustained production of plasma proteins, notably albumin, is a reliable indicator of the differentiated state of hepatocytes. In this work, we have developed a fetal hepatocyte culture system where studying the regulation of albumin expression in proliferating liver cells. Our results show that under proliferative conditions (i.e., in the presence of EGF) fetal hepatocytes maintain albumin production above control quiescent non-treated cells. Glucagon and noradrenaline have no effect on the proliferation induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…As we had previously described that the response of fetal hepatocytes to extracellular stimuli is clearly dependent on their proliferative state, 34 we decided to incubate the cells with dexamethasone (100 nmol/L) in the absence or in the presence of a mitogenic stimulus, i.e., EGF, at 20 ng/mL, and/or TNF-␣. After 10 minutes of stimulation, hepatocytes were lysed and protein extracts were analyzed for JNK activity (Fig.…”
Section: Effect Of Dexamethasone On Jnk Activity Induced By Tnf-␣mentioning
confidence: 99%
“…As we had previously described that the response of fetal hepatocytes to extracellular stimuli is clearly dependent on their proliferative state, 34 we decided to incubate the cells with dexamethasone (100 nmol/L) in the absence or in the presence of a mitogenic stimulus, i.e., EGF, at 20 ng/mL, and/or TNF-␣. After 10 minutes of stimulation, hepatocytes were lysed and protein extracts were analyzed for JNK activity (Fig.…”
Section: Effect Of Dexamethasone On Jnk Activity Induced By Tnf-␣mentioning
confidence: 99%
“…These cells are able to carry out both proliferation and differentiation processes simultaneously. We have shown that some growth factors such as epidermal growth factor (EGF), hepatocyte growth factor, or transforming growth factor-␣ (20,21) are able to induce DNA replication in these cells, whereas some hormones (glucagon, noradrenaline, glucocorticoids), by themselves or in synergism with the positive growth factors, regulate the expression of some liver-specific genes (22)(23)(24). TGF-␤ inhibits the EGF and/or hepatocyte growth factor-induced DNA synthesis and modulates protooncogene and liver-specific gene expression in these cells (20,21,25,26).…”
mentioning
confidence: 99%
“…Analysis of the albuhepatocytes in primary culture respond to epidermal growth factor and hormones (noradrenaline, glucocorti-min and b-actin mRNA levels in livers from rats cotreated with TAM and SAM showed that neither the coids), increasing albumin mRNA level. 12 Growth factors and hormones secreted in response to the TAM-increases in albumin and b-actin mRNA levels at 1 to 2 days nor the decrease in albumin expression at 4 induced hepatotoxicity in the rat 30 could account for the enhanced albumin mRNA levels found under our days (Fig. 2) were observed.…”
Section: Discussionmentioning
confidence: 69%